Pre-pulseless Takayasu Arteritis Presenting with Hypertension - Islam, SM Shaheedul; Nasrin, Sahela; Cader, F Aaysha; Haq, M Maksumul; Md Taimur, Syed Dawood (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Takayasu arteritis (TA) is a chronic granulomatous vasculitic disease of the aorta and its major branches, predominantly affecting young females of Asian origin. Also known as Aortic arch syndrome, the condition has been better documented as the Pulse less disease leading to claudication, bruits, absent or reduced brachial or radial pulses and aortic incompetence. However, a prepulseless stage of TA exists, characterized by non-specific constitutional symptoms, hypertension and raised inflammatory markers. We report the case of an 18- year-old Bangladeshi female presenting with hypertension, moderate to severe aortic regurgitation (AR) and fever, diagnosed and treated as a case of pre-pulseless TA. J Bangladesh Coll Phys Surg 2017; 35(2): 91-96